2012
DOI: 10.1186/1471-244x-12-42
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic polypharmacy in a regional health service: a population-based study

Abstract: BackgroundTo analyse the extent and profile of outpatient regular dispensation of antipsychotics, both in combination and monotherapy, in the Barcelona Health Region (Spain), focusing on the use of clozapine and long-acting injections (LAI).MethodsAntipsychotic drugs dispensed for people older than 18 and processed by the Catalan Health Service during 2007 were retrospectively reviewed. First and second generation antipsychotic drugs (FGA and SGA) from the Anatomical Therapeutic Chemical classification (ATC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
5
19
1
Order By: Relevance
“…For example, hospitalized patients are particularly at risk of experiencing high polypharmacy levels compared with nonhospitalized patients; and also, they are at high risk of adverse events related to polypharmacy. Even among nonhospitalized individuals, whether the population studied is in a clinical or community setting, have a significant impact on the prevalence of reported polypharmacy . The few existing studies that focus on specific medication classes responsible for pediatric polypharmacy are mainly concerned with psychotropic medications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hospitalized patients are particularly at risk of experiencing high polypharmacy levels compared with nonhospitalized patients; and also, they are at high risk of adverse events related to polypharmacy. Even among nonhospitalized individuals, whether the population studied is in a clinical or community setting, have a significant impact on the prevalence of reported polypharmacy . The few existing studies that focus on specific medication classes responsible for pediatric polypharmacy are mainly concerned with psychotropic medications.…”
Section: Introductionmentioning
confidence: 99%
“…Even among nonhospitalized individuals, whether the population studied is in a clinical or community setting, have a significant impact on the prevalence of reported polypharmacy. 12,13 The few existing studies that focus on specific medication classes responsible for pediatric polypharmacy are mainly concerned with psychotropic medications. Therefore, a gap exists when assessing the overall prevalence of polypharmacy in children or the prevalence in other pharmacological groups.…”
Section: Introductionmentioning
confidence: 99%
“…2 Antipsychotic polypharmacy, which has virtually no support in the literature, is now used more frequently than clozapine. 35 …”
Section: Introductionmentioning
confidence: 99%
“…For unclear reasons, homozygotes as a group also have an average ANC that is roughly 1.5×10 3 cells/mm 3 less than groups of heterozygotes or non-carriers, without any evidence of immunocompromise. 3,14,15 By chance, a significant number of these individuals normally have circulating ANC values that fall into a “neutropenic” range as defined by norms created by study of European descent patients. In a large cross-sectional study of 25,222 participants, Hsieh et al 16 reported that 4.5% of African-American participants had an ANC of less than 1.5×10 3 cells/mm 3 versus only 0.79% of European Americans.…”
Section: Introductionmentioning
confidence: 99%
“…PESSOAS Regarding risk factors relating to psychotic polypharmacy, we found that severe mental illness diagnoses were associated with psychotic polypharmacy for both men and women and almost 60% of the patients had severe mental illness diagnosis. The literature describes primary psychiatric diagnosis as one of the most important factors associated with psychotropic polypharmacy: patients with severe mental illnesses such as schizophrenia, depression with psychotic symptoms, and bipolar disorders are at greater risk of polypharmacy and increased use of psychotropic medicines 13,26,30,32,33 .…”
Section: Tablementioning
confidence: 99%